Evidentiality revisited cognitive grammar, functional and discourse-pragmatic perspectives - Marín Arrese, Juana I.; Haßler, Gerda 1953-; Carretero, Marta (John Benjamins Publishing Company, 2017)
Evidentiality Revisited' focuses on semantic-pragmatic based frameworks for the study of evidentials and evidential strategies in European languages (Dutch, English, French, German, Italian, Lithuanian, Portuguese, Russian and Spanish). The book also presents discourse-pragmatic studies, with special emphasis on the use of evidential and epistemic expressions as resources for stancetaking in discourse. The volume addresses issues such as the relationship between the conceptual domains of evidentiality and epistemic modality, the role of evidential and epistemic resources in modelling stancetaking, the expression of speaker commitment to the validity status of the information, and the discourse-pragmatic variation of evidentiality and epistemic modality in discourse domains and genres. The volume offers a collection of contributions in which cross-linguistic studies and corpus-based studies contribute to provide further insights into a usage-based account of linguistic reality
Includes bibliographical references and index
Keywords: Evidentialität; Pragmatik; Kognitive Grammatik; Pragmatics; Cognitive grammar; Aufsatzsammlung